2005
DOI: 10.1038/ncb1250
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIV-1 infection by a small molecule inhibitor of the ATM kinase

Abstract: Chemotherapy that is used to treat human immunodeficiency virus type-1 (HIV-1) infection focuses primarily on targeting virally encoded proteins. However, the combination of a short retroviral life cycle and high mutation rate leads to the selection of drug-resistant HIV-1 variants. One way to address this problem is to inhibit non-essential host cell proteins that are required for viral replication. Here we show that the activity of HIV-1 integrase stimulates an ataxia-telangiectasia-mutated (ATM)-dependent D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
140
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 42 publications
6
140
1
Order By: Relevance
“…Vpr expression enhances the rate of HR, but several reports suggest that NHEJ rather than HR contributes to viral infection (Daniel et al, 1999;Li et al, 2001;Jeanson et al, 2002;Lau et al, 2005). Additionally, Rad52, a cellular component of HR, was shown to work as a suppressive factor for HIV-1 transduction (Lau et al, 2004).…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Vpr expression enhances the rate of HR, but several reports suggest that NHEJ rather than HR contributes to viral infection (Daniel et al, 1999;Li et al, 2001;Jeanson et al, 2002;Lau et al, 2005). Additionally, Rad52, a cellular component of HR, was shown to work as a suppressive factor for HIV-1 transduction (Lau et al, 2004).…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 99%
“…This phenomenon has been explained by delayed progression at the G2/M phase due to DSBs. Additionally, caffeine and caffeine-related methylxanthines are known to impair HIV-1 infection (Nunnari et al, 2005), and an ATM inhibitor, KU55933, is known to decrease the integration of viral DNA into host genome (Lau et al, 2005). These observations suggest that a DSB-induced cellular signal, not HR, is important for viral integration, and that Vpr-induced DSB contributes to efficient viral integration in an ATM-dependent manner.…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the integration of the HIV-1 genome into host chromosomes involves the induction of DNA lesions that lead to the activation of ATM and that rely on ATM-dependent repair processes to be resolved. 38 However, the experimental system used here was virus-free, meaning that other mechanisms must come into action. We speculate that illicit cell fusion that affects proliferating, asynchronous cell populations, leads to a mixture of completely and partially replicated genomes stimulating a massive DNA damage response.…”
Section: Methodsmentioning
confidence: 99%